Microscopic evidence of malaria infection in visceral tissue from medici family, Italy - Maixner, Frank; Drescher, Dennis; Boccalini, Giulia; Piombino-Mascali, Dario; Janko, Marek; Berens-Riha, Nicole; Kim, Bum Jin; Gamble, Michelle; Schatterny, Jolanthe; Morty, Rory E.; Ludwig, Melanie; Krause-Kyora, Ben; et al. (Emerging infectious diseases, 2023)
Microscopic Evidence of Malaria Infection in Visceral Tissue from Medici Family, Italy
Gesehen am 28.09.2023